Juridical Review Indonesian National Army, Army Who Permitted The Crime of Adulture - Wida Susanti; Mohammad Roesli; Adies (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim is to find out the provisions governing the criminal act of violating adultery or immorality committed by the Indonesian National Armed Forces. This research uses the method The type of research in this study is normative juridical law research, namely research based on literature studies which includes primary legal materials and secondary legal materials. Legal Consequences Regarding the crime of violating decency/adultery committed by the Indonesian National Armed Forces, the perpetrator is subject to Article 281 paragraph (1) of the Criminal Code Juncto Article 26 of the Criminal Procedure Code, Article 190 paragraph (1), paragraph (3), paragraph (4) of the Law of the Republic of Indonesia Number 31 of 1997 concerning Military Justice, namely in addition to the main punishment in the form of imprisonment, as well as additional punishment in the form of being dismissed from military service.